Emotion Understanding in Clinically Anxious Children: A Preliminary Investigation - Bender, Patrick K.; Pons, Francisco; Harris, Paul L.; Esbjørn, Barbara H.; Reinholdt-Dunne, Marie L. (Frontiers in Psychology, 2015)
Children’s understanding of the nature, origins and consequences of emotions has been intensively investigated over the last 30-40 years. However, few empirical studies have looked at the relation between emotion understanding and anxiety in children and their results are mixed. The aim of the present study was to perform a preliminary investigation of the relationships between emotion understanding, anxiety, emotion dysregulation, and attachment security in clinically anxious children. A sample of 16 clinically anxious children (age 8-12, 8 girls/boys) was assessed for emotion understanding (Test of Emotion Comprehension), anxiety (Screening for Child Anxiety Related Emotional Disorders-Revised and Anxiety Disorder Interview Schedule), emotion dysregulation (Difficulties in Emotion Regulation Scale) and attachment security (Security Scale). Children who reported more overall anxiety also reported greater difficulties in regulating their emotions, and were less securely attached to their parents. The results also showed that more specific symptoms of anxiety (i.e., OCD and PTSD) correlated not only with emotion dysregulation and attachment insecurity but also with emotion understanding. Finally, there were interrelations among emotion understanding, attachment security, and emotion dysregulation. The present results provide the first comprehensive evidence for a socio-emotional framework and its relevance to childhood anxiety.